Comparing the behaviour of Malaysian financial sector stocks of pre and during the coronavirus outbreak using correlation - Bahari, Nurun Najwa; Muhd Azzimi, Nur Syaza; Ismail, Munira; Bahaludin, Hafizah; Abdul Razak, Fatimah (AIP Publishing, 2024)
The severe and protracted effects of the COVID-19 epidemic pose a significant threat to the economy and the stability of the financial system. It destabilizes the economy and impacts the stock market. We can use the correlation between the stocks to explore the behavior of the stock market, particularly for 50 companies in the financial sector before (2019) and during COVID-19 (2020). The relationship of stocks correlation can be described by the price movement of the stocks. A positive correlation indicate that prices of the stocks are moving in tandem. Meanwhile, negative correlations imply that the price of the stocks are moving in opposite directions. In 2019 before COVID-19 hits, the heatmap of the correlations between the stocks show more negative correlations. Much stronger positive correlations were found in 2020 during COVID-19. It is also found that the banks listed in the financial sector in Bursa Malaysia have a strong positive correlation up to 0.6 during COVID-19. The banks are really important to the financial sector as a capital buffer and financial intermediary specifically during the financial crisis. Hopefully, the results of this study can help investors better understand the impact of COVID-19 on the financial sector in Malaysia.